Windows Vista Secrets: SP1 Edition - Thurrott Paul (American : Wiley, 2008)
Get ready to be amazed by numerous tips, tricks, and undocumented features that disclose unique and exciting aspects of the new Windows Vista SP1 operating system. This revised SP1 Edition is packed with over 250 additional pages revealing secrets on topics like configuring Vista, networking, Microsoft Zune, Windows Live OneCare, LIVE, Windows Home Server, and the new and exciting features included in SP1. Leading Windows authority Paul Thurrott reveals hidden Vista abilities and offers a behind-the-scenes look at everything from hardware and software compatibility to security features to keep your data safe. These priceless pieces of little-known expert advice will help you quickly grasp the many benefits of Windows Vista.
Installing or upgrading to Windows Vista SP1 (see Chapter 2)
Personalizing and configuring Windows Vista SP1 (see Chapter 7)
Windows Vista SP1 networking (see Chapter 10)
Using Zune® as a digital media alternative (see Chapter 12)
Getting the ultimate Vista experience on Tablet PC and Ultra-Mobile PCs (see Chapter 18)
Managing e-mail and contacts (see Chapter 20)
Taking Vista to the next level with LIVE services (see Chapter 21)
Master TV and digital media with Windows Media Center (see Chapter 24)
Keywords: Microsoft Windows; Operating systems